2016
DOI: 10.1016/j.juro.2016.01.107
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Effects of WST11 Vascular Targeted Photodynamic Therapy for Urothelial Cell Carcinoma in Swine

Abstract: Purpose Surgical management of upper tract urothelial carcinoma requires removal of kidney and ureter, compromising renal function. Non-surgical alternatives have potentially prohibitive safety concerns. We examine the feasibility and safety of ablation of the ureter and renal pelvis using endoluminal vascular-targeted photodynamic therapy in a porcine model and report efficacy of WST11 vascular-targeted photodynamic therapy in a murine model. Materials and Methods Following approval, we performed 28 endolum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…In a phase III clinical trial, the treatment was found to be a promising alternative to active surveillance of early stage prostate tumors 6 . PDT with padeliporfin has also proven successful in preclinical in vivo studies with application to renal and urethral tumors 7 , 8 . Furthermore, other photosensitizers were tested for treatment of, amongst others, pancreatic cancer 9 and brain gliomas 10 .…”
Section: Introductionmentioning
confidence: 99%
“…In a phase III clinical trial, the treatment was found to be a promising alternative to active surveillance of early stage prostate tumors 6 . PDT with padeliporfin has also proven successful in preclinical in vivo studies with application to renal and urethral tumors 7 , 8 . Furthermore, other photosensitizers were tested for treatment of, amongst others, pancreatic cancer 9 and brain gliomas 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the authors determined optimal laser fiber distribution, specifically spaced 1 cm apart, and the relationship between laser fluence and the radius of tissue ablation. A companion study similarly confirmed the safety of endoluminal ablation in the ureter and renal pelvis and the intensity dependence of the depth of tissue necrosis [ 24 ]. This investigation further showed that tissue in the irradiated area, in this case, the urothelium, regenerates within 4 weeks with no functional changes.…”
Section: Vtp Mechanism Of Actionmentioning
confidence: 72%
“…It could promote the recruitment of CD8+ T cells in the TME, and the activation of CD8+ T cells could be enhanced by increasing the proportion of DCs in the tumor and upregulating the expression of the costimulatory ligand CD86 on them. 122 Vascular‐targeted photodynamic therapy, which rapidly blocks the associated blood vessels that supply tumor nutrients and leads to tumor necrosis and eradication, 123 also improved cellular immunity in an in‐situ RENCA mouse model of lung metastatic RCC through promoting the infiltration of T cells in the metastatic site and increasing the proportion of CD8+ T cells and CD4+FOXP3‐T cells. 124 Furthermore, cryoablation could improve T cell activity by upregulating IFN‐γ, IL‐10, and GZMB expression and promoting the infiltration of CD8+ T cells at the early stage of RCC, indicating that the combination of cryoablation and anti‐PD‐1 exhibited strong efficacy.…”
Section: Mechanisms Affecting Cellular Immunity In Rccmentioning
confidence: 99%